The Exploration of Antecedent Variables On Occuupational Health And Safety (OHS) Performance at PT. Samudra Oceaneering Batam - Deddy Juniawan Deddy; Amir Fikri; Faizal Madya (Business and Entrepreneurial Review, 2023)
This research was conducted conducted because there are still cases of accidents at PT. Samudra Oceaneering Batam by restricted work category in 2019 which resulted in the victim being unable to carry out his main job and had to be transferred to another job of an administrative nature, and the time lost from the accident is two working days. The consequences of these work accidents not only have an economic and social impact on the company but also have a moral impact on both the employee concerned and his co-workers. This also shows that the achievement of OHS performance has not been maximized by PT. Samudra Oceaneering Batam which can lead to a bad perception of company owners regarding OHS management in the workplace. The aim of this study was to explore the variables that affect the OHS performance at PT. Samudra Oceaneering Batam, so as to reduce the number of work accidents which in turn improves OHS performance. The methodology used in this study uses quantitative methods. The population in this study were all employees of PT. Samudra Oceaneering Batam at all levels with a total of 135 employees and the sample involved in this study was 101 respondents using the Likert scale method. The results of the questionnaire then were processed using SEM SmartPLS. The results of the SmartPLS quantitative data analysis can be concluded that the variable of safety culture has a positive but less significant effect on OHS performance, while employee behavior has a positive and significant effect on OHS performance. Other variables such as leadership style have a positive and significant effect on employee behavior and management commitment has a positive and significant effect on safety motivation. Meanwhile the variable of employee motivation has a negative and insignificant effect on OHS performance.